The films of Lionel Rogosin, Volume 1 [videorecording (DVD)] - Rogosin, Lionel, 1924-2000 (Milestone Film & Video : Distributed by Oscilloscope Laboratories, 2012)
On the Bowery chronicles three days in the drinking life of Ray Salyer which jump-started the post-war American independent film movement, earning an Oscar nomination.